THE ROLE OF THE RUSSIAN LANGUAGE IN TEACHING ENGINEERING STUDENTS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The Russian language plays a significant role in the education of engineering students, particularly in fields where Russia has made substantial contributions, such as aerospace, nuclear energy, and materials science. Despite the dominance of English as the global language of science and technology, Russian remains a valuable tool for accessing a wealth of historical and technical literature, understanding key innovations, and participating in international collaborations. This article explores the importance of Russian language proficiency for engineering students, emphasizing its relevance in both academic and professional contexts. It examines how knowledge of Russian can enhance students’ ability to engage with research, technical documentation, and communicate in multinational projects, particularly in industries with strong Russian involvement. The article also discusses practical approaches to integrating Russian language learning into engineering curricula and the potential benefits for students pursuing careers in global industries.